UBC Mediated by SEPT6 Inhibited the Progression of Prostate Cancer - Ruochen Zhang; Yaojing Yang; Haijian Huang; Tao Li; Liefu Ye; Le Lin; Yongbao Wei (Mediators of Inflammation)
Background. Prostate cancer is one of the most common malignancies in men. Protein ubiquitination is an important mechanism for regulating protein activity and level in vivo. We aimed to study the mechanism of SEPT6 and UBC action in prostate cancer to identify new targets. Methods. The ubiquitin-protein and the ubiquitin coding gene UBA52, UBA80, UBB, and UBC expressions were detected in clinical tissues and cells. Overexpression and knockdown of UBC were performed in prostate cancer DU145 cells. Cell Counting Kit 8 (CCK-8) assay was performed to detect cell proliferation. Cell cycle at 24 h was detected by flow cytometry. Clonal formation assay was used to measure cell clone number. Immunofluorescence (IF) was performed to detect the colocalization of SEPT6 and UBC in prostate cancer cells. Next, we overexpressed or knocked down SEPT6 expression in DU145 cells. Pearson correlation coefficient was applied to analyze the relationship between SEPT6 and UBC in prostate cancer tissue. oe-SEPT6+oe-UBC coexpressing cells were constructed to detect the upstream and downstream relationship between SEPT6 and UBC on prostate cancer cells. The tumor formation experiment was performed to explore SEPT6/UBC effect on prostate cancer. Results. UBC was upregulated in prostate cancer tissues and cells. Overexpression of UBC promoted cell survival and proliferation. IF revealed the colocalization of SEPT6 and UBC in prostate cancer cells. UBC expression decreased after oe-SEPT6, while increased after sh-SEPT6, indicating that UBC was downstream of SEPT6. Pearson correlation coefficient analysis showed that SEPT6 was negatively correlated with UBC in prostate cancer tissues. SEPT6 as an upstream gene of UBC regulated prostate cancer cell behavior through UBC. The tumor formation experiment showed that SEPT6 could inhibit tumor growth. Conclusion. In general, SEPT6 inhibited UBC expression, thereby reducing the overall ubiquitination level, affecting the expression level of downstream cell proliferation-related genes, and then affecting the progression of prostate cancer.